Solutions for the Power Distribution System of Karachi Electric (K- Electric) to Prevent Deaths in Rainy Season - Ali, Hafiz Muhammad Shujahat; Khan, Danish; Ali, Hafiz Muhammad Shafaat; Khan, Ahmed Muddassir; Qazi, Mohsin Ali (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Karachi is the metropolitan city of Pakistan. In rainy or flood season many deaths occurred due to electric shock. For the prevention, we suggest here to K-Electric (Karachi Electric Supply Distribution company) to control death casualties due to electric shock in rainy season. In suggestion paper providing some suggestions to the big power supplier of Karachi (K-Electric) about safety, maintenance, and monitoring for the prevention from deaths occur in metropolitan city due to electric shock. Those deaths occur due to faults in electric pole and touch the fallen live wire. When people touch the pole, they got electric shock in rainy and storm condition due to these electric faults occur in this condition provides enough loss to humans in the form to lose their lives. For the prevention or overcome the loss of life and danger here are giving some suggestions, if do work on following safety, maintenance and monitoring system then get the control on that loss will occur in heavy rain or flood.